Event-triggered quantized H∞ control for networked control systems in the presence of denial-of-service jamming attacks. (August 2019) - Chen, Xiaoli; Wang, Youguo; Hu, Songlin
Abstract: The problem of event-triggered quantized H ∞ control of networked control systems (NCSs) under denial-of-service (DoS) jamming attacks is investigated in this paper. Firstly, a new resilient event-triggering transmission scheme is proposed to lighten the load of computing and communications while offsetting the DoS jamming attacks imposed by power-constrained Pulse-Width Modulated (PWM) jammers. Secondly, a new switched system model is established, which characterizes the effects of the event-triggering scheme, quantization and DoS jamming attacks within a unified framework. Thirdly, linear matrix inequality (LMI)-based sufficient conditions for ensuring the exponential stability of the resulting switched system under the DoS jamming attacks are derived by using the piecewise Lyapunov functional method. Moreover, if the obtained LMIs are feasible, the co-design of the event-triggering parameter and the feedback gain matrix can be obtained. Finally, a satellite yaw angle control system is given to verify the effectiveness and feasibility of the developed theoretical results.